2016
DOI: 10.1155/2016/5271251
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Inhibition of NLRP3 Inflammasome Attenuates Myocardial Ischemia/Reperfusion Injury by Activation of RISK and Mitochondrial Pathways

Abstract: Although the nucleotide-binding oligomerization domain- (NOD-) like receptor pyrin domain containing 3 (NLRP3) inflammasome has been recently detected in the heart, its role in cardiac ischemia/reperfusion (IR) is still controversial. Here, we investigate whether a pharmacological modulation of NLRP3 inflammasome exerted protective effects in an ex vivo model of IR injury. Isolated hearts from male Wistar rats (5-6 months old) underwent ischemia (30 min) followed by reperfusion (20 or 60 min) with and without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(90 citation statements)
references
References 42 publications
3
87
0
Order By: Relevance
“…It was shown to be protective against NLRP3-involved myocardial I/R in a rat model (Mastrocola et al, 2016). Further rigorous investigations are needed to evaluate the effects of INF4E on neurological diseases and its side effects.…”
Section: Targeting the Nlrp3 Inflammasome For The Treatment Of Neurolmentioning
confidence: 99%
“…It was shown to be protective against NLRP3-involved myocardial I/R in a rat model (Mastrocola et al, 2016). Further rigorous investigations are needed to evaluate the effects of INF4E on neurological diseases and its side effects.…”
Section: Targeting the Nlrp3 Inflammasome For The Treatment Of Neurolmentioning
confidence: 99%
“…In 2013, Sandanger et al reported a reduced infarct size in Nlrp3 −/− mice in an ex vivo Langendorff perfused heart model of IR . Also using isolated hearts, it was confirmed that pre‐treatment with the NLRP3 inhibitor, INF4E, reduced infarct size and improved ventricular developed pressure after IR . These findings were confirmed by Luo et al in a type 2 diabetes rat model …”
Section: Pyroptosismentioning
confidence: 75%
“…Despite the fact that IR‐damaged myocardium releases a combination of priming and triggering factors of the NLRP3 inflammasome, it has been proposed that the NLRP3 inflammasome in the heart is not sufficient to respond to a trigger signal in the absence of a priming . Actually, after IR, the size of the infarct is found to increase more in the presence of an active NLRP3, especially if metabolic syndrome has primed the inflammasome …”
Section: Pyroptosismentioning
confidence: 99%
“…The NLRP3 inflammasome is a large multimeric protein complex mediating the cleavage of inactive 414 415 416 417 418 419 420 421 422 423 424 425 426 427 428 429 430 431 432 433 434 435 436 437 438 439 440 441 442 443 444 445 446 447 448 449 450 451 452 453 454 455 456 457 458 459 460 461 462 463 464 465 466 467 468 469 470 471 472 prointerleukin-(IL-) 1 and IL-18 into their active form [94]. We have recently provided evidence that activation of NLRP3 inflammasome contributes to the development of insulin resistance and dietinduced renal and myocardial dysfunctions, mainly by inducing IL-1 and IL-18 overproduction [95][96][97]. Activation of the endothelial NLPR3 inflammasome by injurious adipokines such as visfatin may disrupt inter-endothelial junctions and increase paracellular permeability of the endothelium contributing to the early onset of endothelial injury during metabolic disorders [98].…”
Section: Endothelial Dysfunction and Metaflammationmentioning
confidence: 99%
“…At present, efficacious NLRP3 inflammasome inhibitors are still under development. We recently contributed to characterize the cardiovascular effect of the small molecule INF4E, one of the few compounds that has been demonstrated to directly target the NLRP3 inflammasome and inhibit the ATPase activity of NLRP3 required for its activation [97]. Similar cardiovascular protective effects have been recently documented by using another small molecule which prevents the formation of the NLRP3 inflammasome complex in cardiomiocytes, thus ameliorating cardiac function after ischemia/reperfusion injury [188].…”
Section: Nlrp3 Inflammasome Inhibitors -mentioning
confidence: 99%